(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article observes the issues related to implementation of computer technologies into translation process. The advantages and disadvantages of computer-assisting translation tools are revealed and basing of these findings some recommendations are developed. There is also a brief outline of existing software, which translators may find convenient.